MODEL H-SCORE W BADANIU KONDYCJI MAŁYCH I ŚREDNICH PRZEDSIĘBIORSTW - Kalupa, Łukasz (Wydział Prawa i Administracji UAM, 2001)
The aim of the article is to present an H-score model for small and medium-sized enterprises (SME) developed by J. G. Fulmer, J. E. Moon, T. A. Gavin, and J. M. Erwin. In the background, the SME sector in Poland is presented and evaluated. Its important role in the economy makes the H-score a very interesting tool for Polish institutions analysing small and medium-sized enterprises, especially that the Polish models fail to evaluate the condition of this sector of the market. The paper consists of three parts. The first one presents an analysis of the current situation in the SME sector in Poland. In order to understand the potential usefulness of the model one needs to realise the importance of one’s knowledge about it. The second part of the paper is devoted to the description of the H-score model: the methodology of the study, the sources of the data, the selected variables, the discriminant function, the H-scale of the discriminant scores and a validation of the firm classification. Finally, the third part contains conclusions, especially concerning the potential applications of the H-score model in the Polish economic terms.
H-SCORE MODEL AND ITS USE IN EVALUATION OF THE SMALL AND MIDDLE-SIZED ENTERPRISES PERFORMANCE